The Effect of Perception of Use, Ease, Security and Confidentiality to Use E-Filing (Study In The Tax Office Pratama Raba Bima) (International Journal of Scientific Research and Management (IJSRM), 2018)
The research aim to examine and analyze the effect of perception of use, perception of ease, security and confidentiality to use of e-filing of the corporate taxpayer. The population in this study the number of taxpayers registered in the Tax Office Pratama Raba Bima which consists of Dompu Regency, Bima and Bima City amounted to 350 corporate taxpayers. The sampling technique is done by proportional stratified random sampling of 75 taxpayers. The research instrument is in the form of questionnaire and the data is analyzed with Smart PLS 2.0. The results showed that perception of use, perception of ease, security and confidentiality have positive and significant effect on the use of e-filing.